THE ANALYSIS OF STUDENTS' PREPAREDNESS FOR THE SUBJECT ``CONSTRUCTIONAL MACHINE ELEMENTS'' TAUGHT AT THE FACULTY OF ENGINEERING - KADNAR, Jozef; KADNAR, Milan (Trends in education, 2010)
The aim of the article is to analyse the students' preparedness for the subject ``Constructional Machine Elements'' which is taught at the Faculty of Engineering, Slovak University of Agriculture in Nitra. Based on a questionnaire, the main aim is to evaluate the students' preparedness for the subject.
Keywords: questionnaire; students' preparedness; Constructional Machine Elements.